Mineralocorticoid regulation of cell function: the role of rapid signalling and gene transcription pathways. (January 2017) - Ong, Gregory S Y; Young, Morag J
Abstract : The mineralocorticoid receptor (MR) and mineralocorticoids regulate epithelial handling of electrolytes, and induces diverse effects on other tissues. Traditionally, the effects of MR were ascribed to ligand–receptor binding and activation of gene transcription. However, the MR also utilises a number of intracellular signalling cascades, often by transactivating unrelated receptors, to change cell function more rapidly. Although aldosterone is the physiological mineralocorticoid, it is not the sole ligand for MR. Tissue-selective and mineralocorticoid-specific effects are conferred through the enzyme 11β-hydroxysteroid dehydrogenase 2, cellular redox status and properties of the MR itself. Furthermore, not all aldosterone effects are mediated via MR, with implication of the involvement of other membrane-bound receptors such as GPER. This review will describe the ligands, receptors and intracellular mechanisms available for mineralocorticoid hormone and receptor signalling and illustrate their complex interactions in physiology and disease.